Modest Rise in Caesarean Section from 2000-2010: The Dutch Experience. - Yanjun Zhao; Jun Zhang; Chantal Hukkelhoven; Pien Offerhaus; Joost Zwart; Ank de Jonge; Caroline Geerts (PLoS ONE)
Background The caesarean delivery (CD) rate has risen in most countries over the last decades, but it remains relatively low in the Netherlands. Our objective was to analyse the trends of CD rates in various subgroups of women between 2000 and 2010, and identify the practice pattern that is attributable to the relative stability of the Dutch CD rate. Methods A total of 1,935,959 women from the nationwide Perinatal Registry of the Netherlands were included. Women were categorized into ten groups based on the modified CD classification scheme. Trends of CD rates in each group were described. Results The overall CD rate increased slightly from 14.0% in 2000-2001 to 16.7% in 2010. Fetal, early and late neonatal mortality rates decreased by 40-50% from 0.53%, 0.21%, 0.04% in 2000-2001 to 0.29%, 0.12%, 0.02% in 2010, respectively. During this period, the prevalence of non-vertex presentation decreased from 6.7% to 5.3%, even though the CD rate in this group was high. The nulliparous women with spontaneous onset of labor at term and a singleton child in vertex presentation had a CD rate of 9.9%, and 64.7% of multiparous women with at least one previous uterine scar and a singleton child in vertex presentation had a trial of labor and the success rate of vaginal delivery was 45.9%. Conclusions The Dutch experience indicates that external cephalic version for breech presentation, keeping the CD rate low in nulliparous women and encouraging a trial of labor in multiparous women with a previous scar, could help to keep the overall CD rate steady.